Canadian Cancer Trials Group (CCTG) IND211: A randomized trial of pelareorep (Reolysin) in patients with previously treated advanced or metastatic non-small cell lung cancer receiving standard salvage therapy. (June 2018) - Bradbury, Penelope A.; Morris, Donald G.; Nicholas, Garth; Tu, Dongsheng; Tehfe, Moustapha; Goffin, John R.; Shepherd, Frances A.; Gregg, Richard W.; Rothenstein, Jeffrey; Lee, Christoper; Kuruvilla, Sara; Keith, Bruce D.; et al.
Highlights: Reolysin with chemotherapy did not improve the progression free survival in unselected NSCLC. A three day regimen of pelareorep was found to be tolerable. Exploratory molecular analyses demonstrated a possible association with STK11 or PIK3Ca subtypes. Abstract: Objectives: Pelareorep (reolysin), a Dearing strain of reovirus serotype 3, has demonstrated oncolytic activity as single agent and synergy with chemotherapy. We evaluated pelareorep, combined with standard second-line chemotherapy in patients with non-small cell lung cancer (NSCLC). Materials and methods: This randomized phase II trial enrolled patients with advanced or metastatic NSCLC after first line chemotherapy. After a safety run-in, patients were randomized 1:1 to chemotherapy (pemetrexed [500 mg/m2, non-squamous], or docetaxel [75 mg/m2], day 1 every 21 days]) +/− pelareorep (4.5 × 1010 TCID50, days 1–3 every 21 days), stratified by EGFR mutation status. The primary outcome was progression free survival (PFS) of patients randomized to chemotherapy + pelareorep vs. chemotherapy alone. Secondary outcomes included overall survival, objective response rate and exploratory translational analyses. Results: Between October 2012 and August 2015, 166 patients were enrolled (14 to the safety run in). Pelareorep did not improve the PFS vs. single agent chemotherapy (median PFS 3.0 months, 95% confidence interval [CI] 2.6–4.1) vs. 2.8 months (95% CI 2.5–4.0), hazard ratio (HR) 0.90 (95% CI 0.65–1.25), P  = 0.53). Neither KRAS or EGFR mutation was associated with improved PFS, but STK11 mutations did appear to have an association with improved PFS (HR 0.29 [0.12–0.67); as did PIK3CA mutation (HR 0.45 [0.22–0.93]). The combination was tolerable, although associated with increased rates of neutropenic fever. Conclusion: The addition of pelareorep to second-line chemotherapy did not improve the PFS of patients with NSCLC. The three-day pelareorep schedule was tolerable. Further research is needed to evaluate the potential benefit in molecular subtypes of NSCLC.